Problematika Peserta didik dalam belajar membaca permulaan - Selin Rahmasari; DIdik Tri Setiyoko; Diah Sunarsih (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to describe the difficulties of students in early reading in grade 2 students at SD Negeri Pebatan 03. To describe the factors that inhibit early reading in grade 2 students at SD Negeri Pebatan 03. This study uses qualitative research with research design using a study cases with data collection techniques using observation, interviews, and documentation. The validity of the data is done by triangulation. The triangulation used is technique triangulation and source triangulation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions.Based on the results of the study, it was concluded that: The problems of students in learning to read early are that there are students who have difficulty in learning to read beginning. The difficulties experienced by the second grade students of SD Negeri Pebatan 03 include difficulties in recognizing letters, spelling difficulties, difficulties in assembling the arrangement of letters, and difficulties in punctuation and the factors that hinder students in learning to read early, namely physical factors, school factors , and interest factors.